Histone acetyltransferase promotes fluoride toxicity in LS8 cells. (May 2020) - Deng, Huidan; Fujiwara, Natsumi; Cui, Hengmin; Whitford, Gary M.; Bartlett, John D.; Suzuki, Maiko
Abstract: Previously we demonstrated that fluoride increased acetylated-p53 (Ac-p53) in LS8 cells that are derived from mouse enamel organ epithelia and in rodent ameloblasts. However, how p53 is acetylated by fluoride and how the p53 upstream molecular pathway responds to fluoride is not well characterized. Here we demonstrate that fluoride activates histone acetyltransferases (HATs) including CBP, p300, PCAF and Tip60 to acetylate p53. HAT activity is regulated by post-translational modifications such as acetylation and phosphorylation. HAT proteins and their post-translational modifications (p300, Acetyl-p300, CBP, Acetyl-CBP, Tip60 and phospho-Tip60) were analyzed by Western blots. p53-HAT binding was detected by co-immunoprecipitation (co-IP). Cell growth inhibition was analyzed by MTT assays. LS8 cells were treated with NaF with/without HAT inhibitors MG149 (Tip60 inhibitor) and Anacardic Acid (AA; inhibits p300/CBP and PCAF). MG149 or AA was added 1 h prior to NaF treatment. Co-IP results showed that NaF increased p53-CBP binding and p53-PCAF binding. NaF increased active Acetyl-p300, Acetyl-CBP and phospho-Tip60 levels, suggesting that fluoride activates these HATs. Fluoride-induced phospho-Tip60 was decreased by MG149. MG149 or AA treatment reversed fluoride-induced cell growth inhibition at 24 h. MG149 or AA treatment decreased fluoride-induced p53 acetylation to inhibit caspase-3 cleavage, DNA damage marker γH2AX expression and cytochrome-c release into the cytosol. These results suggest that acetylation of p53 by HATs contributes, at least in part, to fluoride-induced toxicity in LS8 cells via cell growth inhibition, apoptosis, DNA damage and mitochondrial damage. Modulation of HAT activity may, therefore, be a potential therapeutic target to mitigate fluoride toxicity in ameloblasts. Highlights: Fluoride activates histone acetyltransferase (HAT) in enamel organ-derived LS8 cells. HAT inhibitors suppressed fluoride-mediated acetylation of p53 and cell toxicity. Modulation of HAT activity may be a potential target to mitigate fluoride toxicity.